Reasoning over multiple human-human interaction activities - Perez, Mauricio Lisboa (Nanyang Technological University, 2021)
Humans are naturally social, engaging in a wide range of interactions with other individuals. These interaction activities can have multiple people involved or just two individuals, and comprise mutual-actions with diverse degrees of complexity and distinct intentions. Therefore, it is still very challenging for machines to autonomously identify them. In this thesis, we explore and propose different techniques to reason about human interactions under distinct scenarios, and exploit multiple types of data.